Perbandingan Penerapan Media Audiovisual Dan Media Lingkungan Dalam Menulis Puisi Siswa Kelas V SD - Rukayah Rukayah; Abd. Hafid; Sitti Jauhar (Universitas Negeri Makassar, 2020)
This study aims to determine the difference in the effect of the application of audiovisual media and environmental media on the learning outcomes of fifth-grade students to write poetry at SDN No. 24 Macanang, Tanete Riattang Barat District, Bone Regency. This type of research is quasi-experimental, and the research design is Nonequevalent Control Group Design. The research data were collected using tests and documentation and analyzed using descriptive statistics and inferential statistics. The results showed that there were differences in the poetry writing skills of students who learned using audiovisual media and environmental media. This is based on the t-test analysis which shows the application of audiovisual media is higher than the application of environmental media. Although environmental media has a greater contribution to students' knowledge of writing poetry, the difference in the contribution is very small. While in the skill aspect, the contribution of audiovisual media is much greater than environmental media in writing poetry